Displacement of gas bubbles at emerging from the bottom to the sea surface - Lyalko, V. I.; Vorobiev, A. I.; Geykhman, A. M. (Reports of the National Academy of Sciences of Ukraine, 2015)
Displacements of gas bubbles by currents in the sea thickness are analyzed at their emerging and carrying out of cold benthonic waters from the sea bottom to the sea surface that leads to the formation of temperature lowering anomalies, which, at sufficient volumes of gas discharges, can serve as the search criterion of the presence of hydrocarbon deposits. Under the influence of sea currents, there is a lateral displacement of temperature lowering anomalies along the sea surface at distances up to several hundred meters relatively the places of hydrocarbon discharges from the sea bottom. This should be considered during the searches for hydrocarbon deposits on the sea by means of satellite surveys in the thermal range.